40 Transoesophageal echocardiogram findings in STROKE & TIA, their relationship with MRI DWI lesions. (16th October 2019) - Waters, M; Moore, D; Coughlan, JJ; Loo, B
Abstract : Transoesophageal echocardiography (TOE) is frequently performed in patients following a cryptogenic stroke or transient ischaemic attack (TIA). The aim of this single centre study was to determine the diagnostic yield of TOE in cases referred following a stroke or TIA, & to clarify whether findings differed based on evidence of an acute ischaemic cerebral event on MRI or CT. We also sought to assess the prevalence of patent foramen ovale (PFO) in this population and whether they would meet the inclusion and exclusion criteria for recent PFO closure trials. Methods: We retrospectively analysed TOE cases performed in our centre for assessment of an embolic source of a stroke or TIA between November 2017 &amp November 2018. Patients who did not have cerebral imaging in our centre were excluded from this study. Baseline, demographic, clinical, & technical data were collected for all patients using our IT system & a database was formed. Significant findings on TOE were defined as left atrial appendage (LAA) thrombus, left ventricular thrombus, patent foramen ovale & grade 3–4 aortic arch atheroma. Results: Our analysis included 189 TOEs during the study period, 20 of these patients were excluded due to incomplete imaging. The study includes 169 TOE cases. Baseline characteristics of the study included, mean age 60.7 years (range; 23–84), female 50.3%. 49.7% (n=84) of patients had a lesion on MRI with diffusion weighed imaging (DWI +), (DWI + MRI: 49.7% v DWI - MRI: 50.2%) (table 1). Significant findings on TOE were identified more commonly in patients with evidence of an acute lesion on MRI DWI, (47% v 31%, p value=0.01996). 1 left atrial appendage thrombus was identified in a MRI DWI+ case, this required initiation of anticoagulation. A PFO was identified in 13% of cases (n=22). Prevalence of PFO did not differ between the DWI+ and DWI - cohorts (15.4% vs 12.9%, p=NS). Only 13.6% of PFO's identified (n=3, 1.7% of total cohort) were eligible for PFO closure based on hierarchal application of the REDUCE and CLOSE trial criteria. (Table 2). Conclusion: Over half of patients referred for work-up of TOE to rule out an embolic source for a stroke/TIA do not have MRI evidence of an acute ischaemic cerebral event. As such their prior probability of relevant abnormalities being identified on TOE is decreased. Physicians should take this prior probability into account when reporting TOEs in the setting of TIA/Stroke. PFOs were identified in a smaller than expected number of patients in our cohort. Care must be taken when interpreting the significance of a PFO in these patients, particularly in those who do not meet the criteria for PFO closure. We determined a statistically significant increase in diagnostic yield and explanation for TIA/stroke aetiology on TOEs performed in patients with objective evidence of cerebral ischaemia. However TOE identified minimal findings that led to a change in patient therapeutic management.